2020
DOI: 10.33368/woh.v0i0.285
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Petani Padi Dalam Penggunaan Pestisida Di Desa Mandalahurip Kecamatan Jatiwaras Kabupaten Tasikmalaya

Abstract: Pestisida merupakan senyawa kimia, organisme renik, virus dan zat lain-lain yang digunakan untuk melindungi bagian tanaman. Petani mengharapkan hasil dari produk pertanian meningkat sehingga petani menggunakan pestisida untuk menghilangkan hama dan gulma. Akan tetapi, penggunaan pestisida memiliki efek samping yang negatif yaitu berkurangnya keanekaragaman hayati dan dapat membunuh makhluk yang bukan sasarannya. Penelitian ini bertujuan mengetahui hubungan pengetahuan, sikap, umur, tingkat pendidikan dan masa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
2
1
2
Order By: Relevance
“…The Agricultural Extension Officer in Ambarawa District confirmed that the positive attitude of the community is not always followed by positive behavior. The results of this study are not in accordance with the results of research by Suryani & Pratamasari (2020) which states that attitudes are related to behavior. Because the internal factors of farmers in Ambarawa district that are most influential are the fulfillment of their needs and business constraints, the intense disturbance of pests (plant pests) raises concerns for farmers, thus encouraging farmers to act impulsively in the application of insecticides to avoid crop failure.…”
Section: Community Attitudes In Insecticide Resistance Managementcontrasting
confidence: 99%
See 1 more Smart Citation
“…The Agricultural Extension Officer in Ambarawa District confirmed that the positive attitude of the community is not always followed by positive behavior. The results of this study are not in accordance with the results of research by Suryani & Pratamasari (2020) which states that attitudes are related to behavior. Because the internal factors of farmers in Ambarawa district that are most influential are the fulfillment of their needs and business constraints, the intense disturbance of pests (plant pests) raises concerns for farmers, thus encouraging farmers to act impulsively in the application of insecticides to avoid crop failure.…”
Section: Community Attitudes In Insecticide Resistance Managementcontrasting
confidence: 99%
“…Farmers' knowledge of resistance management is still low, because it does not comply with the guidelines for insecticide resistance management issued by the Ministry of Agriculture. The results of this study are in line with Suryani & Pratamasari, (2020) which states that most farmers, namely more than 50% of farmers, have insufficient knowledge in insecticide resistance management practices, insufficient knowledge causes farmer behavior in the practice of using insecticides as desired without thinking about the consequences or the effects of improper use of insecticides.…”
Section: Resultssupporting
confidence: 84%
“…3 Pestisida merupakan substansi (zat) kimia, organisme renik, virus, dan zatzat lain yang digunakan oleh petani untuk melindungi tanaman. 4 Jenis-jenis pestisida yang saat ini umum digunakan oleh petani yaitu organofosfat, karbamat dan piretroid. Dampak pestisida bagi lingkungan yaitu dapat mengancam kehidupan biota-biota yang hidup di dalam tanah akibat residu pestisida di dalam tanah, selain itu apabila residu pestisida terbawa air dan masuk ke dalam sungai, maka biota air juga akan terancam mati.…”
Section: Pendahuluanunclassified
“…Pesticides have been used to eliminate pests and weeds in the last few decades with the intention of increasing agricultural product production could improve (Popp, 2018). Still, farmers can be poisoned by pesticides during mixing, loading, spraying, and cleaning equipment since the active substances in pesticide products could have serious health consequences (e.g., mild or severe intoxication), not to mention the long-term health effects because pesticides do not have specific toxic effects (Sapbamrer & Thammachai, 2020;Suryani et al, 2020;Tarmure et al, 2020). Most people die from exposure to pesticides every year worldwide.…”
Section: Introductionmentioning
confidence: 99%